2016
DOI: 10.1007/s00125-016-4079-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and incident type 2 diabetes mellitus: a systematic review and dose–response meta-analysis of prospective cohort studies

Abstract: Aims/hypothesis Inverse associations between physical activity (PA) and type 2 diabetes mellitus are well known. However, the shape of the dose-response relationship is still uncertain. This review synthesises results from longitudinal studies in general populations and uses non-linear models of the association between PA and incident type 2 diabetes. Methods A systematic literature search identified 28 prospective studies on leisure-time PA (LTPA) or total PA and risk of type 2 diabetes. PA exposures were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
230
5
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 291 publications
(274 citation statements)
references
References 79 publications
13
230
5
6
Order By: Relevance
“…Seasonality of birth has been demonstrated for many aspects of metabolic syndrome, including high systolic blood pressure [82], obesity [83,84] and also dyslipidaemia, insulin resistance and CVD [85]. The seasonal pattern of birth for childhood autoimmune (type 1) diabetic patients was reported repeatedly (see, e.g., [96]), while the seasonality of birth for T2D adult persons was observed only in a few studies.…”
Section: Seasonality Of Birthmentioning
confidence: 99%
“…Seasonality of birth has been demonstrated for many aspects of metabolic syndrome, including high systolic blood pressure [82], obesity [83,84] and also dyslipidaemia, insulin resistance and CVD [85]. The seasonal pattern of birth for childhood autoimmune (type 1) diabetic patients was reported repeatedly (see, e.g., [96]), while the seasonality of birth for T2D adult persons was observed only in a few studies.…”
Section: Seasonality Of Birthmentioning
confidence: 99%
“…The relationship in this analysis was curvilinear between the two factors. The authors found a risk reduction of 26% for type 2 diabetes among people who achieved about 11.25 MET (metabolic equivalent of task) hours per week (equivalent to 150 min per week of moderate activity) relative to inactive individuals (6).…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 98%
“…shows that greater health gains are accrued from increasing leisure-time PA compared with total PA (344). In addition, gains from vigorous PA were found to be higher than from moderate and total PA.…”
Section:  Improve Dose-response For the Association Of Pa And Healthmentioning
confidence: 81%
“…A limitation of this and similar studies (175) results from not knowing the exact shape of the association PA-health. Recent studies assessing the association of PA with health and using continuous exposure indicate greatest benefits at low levels of PA (48,344). The level of ambient air pollution in Brisbane is one of the lowest observed in the world (345), and relative risks for PM2.5 are based on data from more polluted locations, resulting in uncertainty at the lowest part of the exposure-response relationship (88).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation